Autologous hematopoietic stem cell transplantation in the treatment of systemic sclerosis. Part 1. Clinical aspects - O. B. Ovsyannikova; L. P. Ananyeva; O. A. Koneva; L. A. Garzanova; R. U. Shayakhmetova; O. V. Desinova; M. N. Starovoitova; A. M. Lila (Современная ревматология, 2020)
Diffuse cutaneous systemic sclerosis (SSc) characterized by an acute, rapidly progressive course and severe damage to the internal organs has an unfavorable prognosis, while the treatment of this often fatal type of the disease has not been sufficiently developed. This paper reviews an update on an autologous hematopoietic stem cell transplantation (auto-HSCT) procedure, transplantation stages, and conditioning modes in patients with SSc. It presents the characteristics of auto-HSCT studies conducted in 2005 to 2016. The inclusion and exclusion criteria used in these studies are described and their outcomes compared. The results of three randomized controlled trials concerning auto-HSCT are analyzed separately. These findings confirm that auto-HSCT is currently more effective than standard immunosuppressive therapy. Auto-HSCT produces better results that can provide a more favorable long-term prognosis of SSc; it can prevent worsening of organ damages and improve skin scores and lung function. Patients with early diffuse SSc, a rapidly progressive course, and poor prognostic factors in the first 4–5 years of the disease before the development of functional insufficiency of the vital organs can be considered most promising for auto-HSCT.